Current State of Surgical Lighting - Curlin, Jahnavi; Herman, Charles K. (The Surgery Journal, 2020)
Surgical performance in the operating room (OR) is supported by effective illumination, which mitigates the inherent environmental, operational, and visual challenges associated with surgery. Three critical components are essential to optimize operating light as illumination: (1) centering on the surgeon's immediate field, (2) illuminating a wide or narrow field with high-intensity light, and (3) penetrating into a cavity or under a flap. Furthermore, optimal surgical illumination reduces shadow, glare, and artifact in visualization of the surgical site. However, achieving these principles is more complex than at first glance, requiring a detailed examination of the variables that comprise surgical illumination. In brief, efficacious surgical illumination combines sufficient ambient light with the ability to apply focused light at specific operative stages and angles. But, brighter is not always merely better; rather, a nuanced approach, cognizant of the challenges inherent in the OR theater, can provide for a thoughtful exploration of how surgical illumination can be utilized to the best of its ability, ensuring a safe and smooth surgery for all.
Keywords: surgical lighting; disposable instruments; lighted retractors; skin burns; overhead lighting